Measurement Uncertainty in Fire Tests— A Fire Laboratory Point of View - Trevino, Javier O.; Curkeet, Rick (Uncertainty in Fire Standards and What to Do About It, 2012)
Since the adoption of ISO/IEC 17025, testing laboratories have been required to perform Measurement Uncertainty analysis for the tests within their scope. Four points of recurring debate are discussed: (1) The variability in fire test results due to unforeseen/uncontrolled variables is generally far greater than the measurement uncertainty of the result. (2) It is important not to confuse “measurement uncertainty” (MU) with “precision” of results. MU has a very specific meaning as used in ISO/IEC 17025, ISO/IEC Guide 98-3 Guide to the Expression of Uncertainty in Measurement (GUM) and ISO Guide 99 International vocabulary of metrology—Basic and general concepts and associated terms (VIM). (3) An uncertainty result is not used to justify passing or failing a product with results very near the pass/fail limit. Where the measured result is subject to a measurement uncertainty evaluation and reporting, compliance limits may or may not require extending the test result by the MU value in making a compliance determination. (4) ISO/IEC 17025 specifically exempts standards that specify limits on sources of uncertainty and specify the form of reporting from a required MU statement. This makes uncertainty estimates inapplicable to those fire tests.